Coiled coils 9-to-5: rational de novo design of α-helical barrels with tunable oligomeric states. Issue 20 (20th April 2021) - Dawson, William M.; Martin, Freddie J. O.; Rhys, Guto G.; Shelley, Kathryn L.; Brady, R. Leo; Woolfson, Derek N.
Abstract : Systematic de novo design of peptides that form α-helical barrels with functionalisable central channels with a range of internal diameters. Abstract : The rational design of linear peptides that assemble controllably and predictably in water is challenging. Short sequences must encode unique target structures and avoid alternative states. However, the non-covalent forces that stabilize and discriminate between states are weak. Nonetheless, for α-helical coiled-coil assemblies considerable progress has been made in rational de novo design. In these, sequence repeats of nominally hydrophobic ( h ) and polar ( p ) residues, hpphppp, direct the assembly of amphipathic helices into dimeric to tetrameric bundles. Expanding this pattern to hpphhph can produce larger α-helical barrels. Here, we show that pentameric to nonameric barrels are accessed by varying the residue at one of the h sites. In peptides with four L/I–K–E–I–A–x–Z repeats, decreasing the size of Z from threonine to serine to alanine to glycine gives progressively larger oligomers. X-ray crystal structures of the resulting α-helical barrels rationalize this: side chains at Z point directly into the helical interfaces, and smaller residues allow closer helix contacts and larger assemblies.